The Y‐STR landscape of coastal southeastern Han: Forensic characteristics, haplotype analyses, mutation rates, and population genetics. Issue 16 (28th May 2021) - Fan, Haoliang; Zeng, Ying; Wu, Weiwei; Liu, Hong; Xu, Quyi; Du, Weian; Hao, Honglei; Liu, Changhui; Ren, Wenyan; Wu, Weibin; Chen, Ling; Liu, Chao
Abstract: The Y‐STR landscape of Coastal Southeastern Han (CSEH) living in Chinese southeast areas (including Guangdong, Fujian, and Zhejiang provinces) is still unclear. We investigated 62 Y‐STR markers in a reasonably large number of 1021 unrelated males and 1027 DNA‐confirmed father‐son pairs to broaden the genetic backgrounds of CSEH. In total, 85 null alleles, 121 off‐ladder alleles, and 95 copy number variants were observed, and 1012 distinct haplotypes were determined with the overall HD and DC values of 0.999974 and 0.9912. We observed 369 mutations in 76 099 meiotic transfers, and the average estimated Y‐STR mutation rate was 4.85 × 10 –3 (95% CI, 4.4 × 10 –3 –5.4 × 10 –3 ). The Spearman correlation analyses indicated that GD values ( R 2 = 0.6548) and average allele sizes ( R 2 = 0.5989) have positive correlations with Y‐STR mutation rates. Our RM Y‐STR set including 8 candidate RM Y‐STRs, of which DYS534, DYS630, and DYS713 are new candidates in CSEH, distinguished 18.52% of father–son pairs. This study also clarified the population structures of CSEH which isolated in population‐mixed South China relatively. The strategy, SM Y‐STRs for familial searching and RM Y‐STRs for individual identification regionally, could be applicable based on enough knowledge of the Y‐STR mutability of different populations.